Discrete Element Analysis of Ice-Induced Vibrations of Offshore Wind Turbines in Level Ice - Xue Long; Lu Liu; Shunying Ji (Journal of Marine Science and Engineering, 2023)
Self-excited vibrations of offshore structures interacting with sea ice, characterized by low frequency and high amplitudes, pose significant hazards to offshore wind turbines (OWTs) in cold seas. This study employs the discrete element method (DEM) with a parallel bonding model to investigate the interaction between sea ice and OWTs. Two bond-failure models are compared, with the results showing that the model considering stiffness softening and fracture energy provides better alignment with field data in the Bohai Sea. The DEM is employed to analyze the ice-induced vibration of OWTs under varying ice velocities, revealing that brittle failure of sea ice occurs at higher ice speeds, leading to random structure vibration. At slower ice speeds, both brittle and ductile sea ice failure modes result in self-excited vibrations. This suggests a strong connection between self-excited vibration and the brittle-ductile failure of sea ice, influenced by the relative speeds between ice and the structure. This study employs the DEM to elucidate the mechanism of self-excited vibrations in OWTs from the perspective of brittle-ductile sea ice failure. The results show that the DEM model accurately describes the brittle-ductile transition in sea ice failure, and that the structural motion aligns well with field measurements.